Tourism Development Strategy Post Covid-19 Pandemic In Kendari City - Sawaludin Sawaludin; Noor Husna Khairisa; Arif Arif (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2023)
Kendari City is a developing city and has many tourism objects. The Covid-19 pandemic that has occurred since March 2020 has caused a lockdown and physical distancing policy, thus impacting the tourism industry. Therefore, there is a need for a tourism development strategy post the Covid-19 pandemic in Kendari City. This study aims to: (1) Know the impact of Covid-19 on the tourism industry in Kendari City; (2) Formulate a tourism development strategy post Covid-19 pandemic in Kendari City. This study uses SWOT analysis. The results of this study are: (1) The impact of Covid-19 in Kendari City, namely a reduction in the number of workers (layoffs), a decrease in the number of visitors in both tourism objects and hotels, a decrease in demand for the provision of meeting rooms, closure of culinary business places, restrictions on the number of visitors, and a decrease in the number of entrepreneurs' income in various fields of tourism; (2) Strategies that can be carried out for tourism development, namely: increasing the promotion of various tourist attractions (including hotels) through social media, collaborating with the government or the private sector to improve the quality and prepare facilities and infrastructure that do not build yet, holding entertainment events, building tourism management community, adding supporting facilities to attract visitors, improving quality and quantity, and diversify menus for culinary tourism, organizing sales areas and improving security at tourist attractions. Keywords: Covid-19, Development Strategy, Tourism